Physical, structural and performance analyses for conformity of polymeric paints and other products / Norsyazlin Abd Rashid - Abd Rashid, Norsyazlin (2023)
Several improvements on the experimental procedures, data processing and results interpretation were done for various types of paints in different storage times and storage conditions for the practicality of the FTIR conformity analysis of the polymeric paint. The reproducibility and reliability of the results from FTIR conformity analysis were then supported with statistical test, physical test and performance test. In this study, four protective coating systems with several industry grade of raw materials and its polymeric paints, which are commonly used in oil and gas industry were collected from five reputable paint manufacturers. The first section of the study describes the process in determining the suitable method to be implemented as an additional QA/QC practice for protective paints. Based on the data analysis from several scientific analyses (i.e. TGA, DSC, Raman, Far-IR), ATR-FTIR is still more practical and cost effective to be used for monitoring the paint quality, either in the testing laboratory as well as on-site verification.